Economics and "The Possibility of Civilization": Four Judgments - Robinson, Dwight E. (Quarterly Journal of Economics, 1953)
Introduction, 50. — Clive Bell's Civilization, 54. — Brooks Adams' Law of Civilization and Decay, 59. — Arnold J. Toynbee's Study of History, 61. — T. S. Eliot's Notes Towards the Definition of Culture, 66. — Conclusion, 70.